Systemic and cerebral iron homeostasis in ferritin knock-out mice. - Wei Li; Holly J Garringer; Charles B Goodwin; Briana Richine; Anthony Acton; Natalia VanDuyn; Barry B Muhoberac; Jose Irimia-Dominguez; Rebecca J Chan; Munro Peacock; Richard Nass; Bernardino Ghetti; et al. (PLoS ONE)
Ferritin, a 24-mer heteropolymer of heavy (H) and light (L) subunits, is the main cellular iron storage protein and plays a pivotal role in iron homeostasis by modulating free iron levels thus reducing radical-mediated damage. The H subunit has ferroxidase activity (converting Fe(II) to Fe(III)), while the L subunit promotes iron nucleation and increases ferritin stability. Previous studies on the H gene (Fth) in mice have shown that complete inactivation of Fth is lethal during embryonic development, without ability to compensate by the L subunit. In humans, homozygous loss of the L gene (FTL) is associated with generalized seizure and atypical restless leg syndrome, while mutations in FTL cause a form of neurodegeneration with brain iron accumulation. Here we generated mice with genetic ablation of the Fth and Ftl genes. As previously reported, homozygous loss of the Fth allele on a wild-type Ftl background was embryonic lethal, whereas knock-out of the Ftl allele (Ftl-/-) led to a significant decrease in the percentage of Ftl-/- newborn mice. Analysis of Ftl-/- mice revealed systemic and brain iron dyshomeostasis, without any noticeable signs of neurodegeneration. Our findings indicate that expression of the H subunit can rescue the loss of the L subunit and that H ferritin homopolymers have the capacity to sequester iron in vivo. We also observed that a single allele expressing the H subunit is not sufficient for survival when both alleles encoding the L subunit are absent, suggesting the need of some degree of complementation between the subunits as well as a dosage effect.